ERCC1-expressing circulating tumor cells as a potential diagnostic tool for monitoring response to platinum-based chemotherapy and for predicting post-therapeutic outcome of ovarian cancer - Chebouti, Issam; Kuhlmann, Jan Dominik; Buderath, Paul; Weber, Stephan; Wimberger, Pauline; Bokeloh, Yvonne; Hauch, Siegfried; Kimmig, Rainer; Kasimir-Bauer, Sabine (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.13286 Issam Chebouti, Jan Dominik Kuhlmann, Paul Buderath, Stephan Weber, Pauline Wimberger, Yvonne Bokeloh, Siegfried Hauch, Rainer Kimmig, Sabine Kasimir-Bauer